IMPLEMENTASI KEBIJAKAN PENGUATAN PENDIDIKAN KARAKTER DI SD AL-RASYID PEKANBARU: Kebijakan Pendidikan - UMRI PEKANBARU, Futri Zaharah (JURNAL ISLAMIKA, 2023)
This study aims to describe the Implementation of Character Education Strengthening Policy (PPK) at SD AL-RASYID Pekanbaru. This type of research is descriptive qualitative using a case study approach. The results showed that the implementation of the Character Education Strengthening Policy at SD AL-RASYID Pekanbaru was carried out through 3 stages, namely; (1) Interpretation of character education strengthening policies that have been carried out by making character education strengthening programs and regulations (2) Organizing structured character education strengthening policies (3) The application of character education strengthening policies is supported by infrastructure facilities. The character values instilled are religious, nationalist, independent, orderly, cooperation, mutual assistance, and integrity. As well as the implementation of KDP policies at SD AL-RASYID can apply in strengthening character education carried out by integrating it in the learning process / KBM, school culture, and extracurriculars. At the implementation stage of the policy of strengthening character education at SD AL-RASYID which is implemented through various activities involving the roles of schools, parents, and the surrounding community so that the three parties have a reciprocal relationship by fulfilling achievements for the golden generation for Indonesia in the future.